2013
DOI: 10.1371/journal.pntd.0002257
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Activates Membrane TRAIL Relocalization and IFN-α Production by Human Plasmacytoid Dendritic Cells In Vitro and In Vivo

Abstract: BackgroundDengue displays a broad spectrum of clinical manifestations that may vary from asymptomatic to severe and even fatal features. Plasma leakage/hemorrhages can be caused by a cytokine storm induced by monocytes and dendritic cells during dengue virus (DENV) replication. Plasmacytoid dendritic cells (pDCs) are innate immune cells and in response to virus exposure secrete IFN-α and express membrane TRAIL (mTRAIL). We aimed to characterize pDC activation in dengue patients and their function under DENV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 79 publications
(103 reference statements)
3
58
0
1
Order By: Relevance
“…6A). Previously, sTRAIL has been attributed to an antiviral mechanism in dengue, given by the induction of apoptosis or the production of type I IFN (47), reducing the cellular viral burden (35) and thus explaining the higher levels of sTRAIL found in children who did not develop severe forms of the infection (Fig. 6A) (36,48).…”
Section: Discussionmentioning
confidence: 96%
“…6A). Previously, sTRAIL has been attributed to an antiviral mechanism in dengue, given by the induction of apoptosis or the production of type I IFN (47), reducing the cellular viral burden (35) and thus explaining the higher levels of sTRAIL found in children who did not develop severe forms of the infection (Fig. 6A) (36,48).…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, Trail − / − mice are unable to clear an IAV infection as well as wild-type mice, and Trail − / − mice are more susceptible to death from immunopathology after IAV infection (Brincks et al, 2008; Brincks et al, 2011). Additional data report increased TRAIL expression after infection with Dengue virus, hepatitis virus, human immunodeficiency virus, measles virus, respiratory syncytial virus, and West Nile virus contributes to both viral clearance and immunopathology (Bem et al, 2010; Stegmann et al, 2010; van Grevenynghe et al, 2011; Barblu et al, 2012; Shrestha et al, 2012; Abdullah et al, 2013; Gandini et al, 2013; Gras et al, 2013; Werner et al, 2013; Brost et al, 2014; Limonta et al, 2014). …”
Section: Immunotherapy Involving Trail Receptor Agonists In Non-camentioning
confidence: 98%
“…Rather than autoantibody-induced cell death, several studies have focused on the apoptosis that is directly induced by DENV infections (52)(53)(54). Studies have demonstrated that DENV infections elicit proapoptotic responses involving the suppression of Bcl-2 and Bcl-x L as well as the induction of Bax (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%